Pregnancy-related anxiety: A concept analysis. (March 2016) - Bayrampour, Hamideh; Ali, Elena; McNeil, Deborah A.; Benzies, Karen; MacQueen, Glenda; Tough, Suzanne
Abstract: Objectives: Evidence suggests that pregnancy-related anxiety is more strongly associated with maternal and child outcomes than general anxiety and depression are and that pregnancy-related anxiety may constitute a distinct concept. However, because of its poor conceptualization, the measurement and assessment of pregnancy-related anxiety have been limited. Efforts to analyze this concept can significantly contribute to its theoretical development. The first objective of this paper was to clarify the concept of pregnancy-related anxiety and identify its characteristics and dimensions. The second aim was to examine the items of current pregnancy-related anxiety measures to determine the dimensions and attributes that each scale addresses, noting any gaps between the current assessment and the construct of the concept. Design: A concept analysis was conducted to examine the concept of pregnancy-related anxiety. Data sources: To obtain the relevant evidence, several databases were searched including MEDLINE, PsycINFO, EBSCO's SocINDEX, Psychological and Behavioral Sciences Collection, CINAHL, SCOPUS, and EMBASE. Review methods: A modified approach based on Walker and Avant (Strategies for theory construction in nursing. 5th ed; 2011) was used. Qualitative or quantitative studies published in English that explored or examined anxiety during pregnancy or its dimensions prospectively or retrospectively were included. Results: Thirty eight studies provided data for the concept analysis. Three critical attributes (i.e., affective responses, cognitions, and somatic symptoms), three antecedents (i.e., a real or anticipated threat to pregnancy or its outcomes, low perceived control, and excessive cognitive activity, and four consequences (i.e., negative attitudes, difficulty concentrating, excessive reassurance-seeking behavior, and avoidance behaviors) were identified. Nine dimensions for pregnancy-related anxiety were determined, and a definition of the concept was proposed. The most frequently reported dimensions included anxiety about fetal health, fetal loss, childbirth, and parenting and newborn care. The content of five scales was analyzed to determine the attributes and dimensions measured by each tool. Our findings suggest that the Pregnancy-Related Anxiety Scale tapping five dimensions of pregnancy-related anxiety and the Pregnancy Outcome Questionnaire with six items pertaining to the consequences of pregnancy-related anxiety can respectively be considered the most useful tools for assessing the existence and severity of the concept. Conclusions: The critical attributes of pregnancy-related anxiety are similar to those defined for anxiety disorders. However, the behavioral consequences of pregnancy-related anxiety appear to apply only some women and may serve as important indicators of the severity of the condition. Current tools are useful instruments to determine whether the concept exists and to capture selected domains of pregnancy-related anxiety. A tool that includes all dimensions of the concept and examines the severity of pregnancy-related anxiety is needed.